2013
DOI: 10.1111/cei.12100
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor-α plus interleukin-10 low producer phenotype predicts acute kidney injury and death in intensive care unit patients

Abstract: SummaryGenetic polymorphism studies of cytokines may provide an insight into the understanding of acute kidney injury (AKI) and death in intensive care unit (ICU) patients. The aim of this study was to investigate whether the genetic polymorphisms of -308 G < A tumour necrosis factor (TNF)-a, -174 G > C interleukin (IL)-6 and -1082 G > A IL-10 may predispose ICU patients to the development of AKI and/or death. In a prospective nested case-control study, 303 ICU patients and 244 healthy individuals were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 30 publications
4
28
0
1
Order By: Relevance
“…In the rat severe burn model, the mRNA level of TNF-α, IL-1β and ICAM-1 in renal tissue was increased significantly. On the contrary, the level of IL-10, an anti-inflammatory cytokine3940, was significantly suppressed in the kidney of severely burned rats and recovered after the administration of melatonin. Based on the results we deduced that melatonin could attenuate the inflammatory response through inhibiting the expression of pro-inflammatory cytokines and up-regulating the expression of anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 95%
“…In the rat severe burn model, the mRNA level of TNF-α, IL-1β and ICAM-1 in renal tissue was increased significantly. On the contrary, the level of IL-10, an anti-inflammatory cytokine3940, was significantly suppressed in the kidney of severely burned rats and recovered after the administration of melatonin. Based on the results we deduced that melatonin could attenuate the inflammatory response through inhibiting the expression of pro-inflammatory cytokines and up-regulating the expression of anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 95%
“…Secreted by immunocytes, TNF-α, IL-1β and IL-6 are involved in the activation of macrophages, lymphocytes and cytotoxic cells; leukocyte/endothelial adhesion; and the induction of acute-phase protein[ 1 ]. In particular, IL-10 is a negative-regulator cytokine generated by immunocytes that antagonises the inflammatory response and regulates autoimmune activity [ 39 ]. The tissue level of IL-10 is usually elevated as an intrinsic anti-inflammatory system responding to exogenous stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the low-producing genotypes of the aforementioned polymorphisms were associated with the risk of AKI, as were the haplotypes T-C-A of TNFA and C-A-C-G of IL-10 . Dalboni et al [ 41 ] showed that the GG genotype of TNFA − 308 polymorphism and AA genotype of IL-10 –1082 polymorphism, when combined, are associated with AKI and/or death, and also with RRT and/or death. Susantitaphong et al [ 30 ] found that TNFA gene −308 G/A A-allele was associated with higher peak serum creatinine and urinary kidney injury molecule-1 (KIM-1), as well as higher multi organ failure (MOF) score in hospitalized patients with AKI.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, associations found with such an approach have been difficult to replicate and the coverage of genetic variation has been poor [ 51 ]. Regardless of some reported positive associations [ 22 , 24 , 25 , 27 35 , 38 , 40 , 41 , 44 50 ], no conclusive data on predisposing genetic variants exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation